Sustainable food production with greenhouse technologies - Gonda, Gy.; Mubarak Al-AliNoor, Y. M.; Fekete-Farkas, M.; Helyes, L. (International Journal of Horticultural Science, 2014)
The greenhouse fruit and vegetable production is one important area which supports sustainability. To achievesustainable economy and growth, the given natural resources have to be used in a smarter, renewable way in order to avoiddepleting them. New technologies and new methods are developed and implemented to utilize resources in more optimized way.Sustainable food supply is essential globally for the world, however it has to be managed and achieved on local levels. We presentthe greenhouse production market restructuring with new players. What kind of difficulties arise in the open field vegetableproduction and what benefits can be realized by the customers and producers from the covered greenhouse technology in thecontinental and desert climate? What are the technical boundary conditions to establish and operate greenhouse production indifferent regions and what are the benefits realized from local food production? As an example, we analyse Qatar’s energetics,climate conditions and food resources, Qatar’s food supply process and its barriers. We will show how the sustainability andfood safety appear in Qatar’s National Strategy Plan.